Reverse Phase High Performance Liquid Chromatography Analysis of Formoterol Fumarate in Bulk and ItsPharmaceutical Formulations - Prasada Rao, K.V.S.; Neelima, B.; Vijaya Kumar, G.; Srinivas, L.D.; Prabhakar, G. (Asian Journal of Chemistry, 2010)
A sensitive reverse phase high performance liquid chromatographic (RP-HPLC) method has been developed and validated for the assay of formoterol fumarate in bulk and its pharmaceutical formulations. The separation was achieved by isocratic elution using a hypersil BDS C-18 (250×4.6 mm) column, using bambuterol as internal standard in a mobile phase consisting of ammonium acetate (50 mM, pH 5.0)-ethanol (60:40, v/v), a flow rate of 1.0 mL/min and UV detection at 242 nm. The detection and quantitation lits were 0.05 and 0.15 μg/mL, respectively, while the linear range of detection was between 0.1 and 100 μg/mL. The results of analysis were treated statistically, as per International Conference on Harmonization (ICH) guidelines for validation of analytical procedures and by recovery studies. The study shows that the proposed method is an accurate, linear and sensitive assay method for formoterol fumarate in bulk and its pharmaceutical formulations.